Answer:
11
Step-by-step explanation:
3+7=10
4/8=1/2
12+1/2=1
10+1=11
Answer:
Express the given function h as a composition of two functions f and g so that h (x )equals (f circle g )(x )commah(x)=(f g)(x), where one of the functions is 4 x minus 3.4x−3. h (x )equals (4 x minus 3 )Superscript 8h(x)=(4x−3)8 f (x )f(x)equals=4 x minus 3. See answer. zalinskyerin2976 is waiting for your help.
Step-by-step explanation:
this what f ;|
Answer:
(13 + or - (sign) square root(37)) / 6
Step-by-step explanation:
First search up the quadratic formula which is
x = (- b + or - square root(b^2 - 4ac)) / 2a
and to find a, b, and c you need this formula
ax^2 + bx + c = 0 (btw this is the safest solution to finding your answer with a number in-front of a quadratic equation.)
Math:
a = 3, b = -13, c = 11
b = -13, because of the x on the other end of the equation as the equation above "ax^2 + bx + c = 0" you need the zero to proceed to this next step.
Side Note: You only take the number and not the variable, variables are x, y, w, z, or etc.
(- (- 13) + or - square root((-13)^2 - 4(3)(11) ) ) / 2 * 3
13 + or - square root(37) / 6
Answer:
Raise 4 4 to the power of 2 2 . Simplify 11+(4)2 11 + ( 4 ) 2 . Raise 4 4 to the power of 2 2 . Add 11 11 and 16 16 .
Step-by-step explanation: